Curvature of iris profile in spectral domain optical coherence tomography and dependency to refraction, age and pupil size – the MIPH Eye&Health Study. Issue 2 (4th August 2016) - Schuster, Alexander K.; Fischer, Joachim E.; Vossmerbaeumer, Urs
Abstract: Purpose: Optical coherence tomography (OCT) of the anterior segment allows quantitative analysis of the geometry of the iris. We performed spectral domain OCT examinations in healthy emmetropic, hyperopic and myopic subjects to investigate iris curvature and its associations. Methods: In a cross‐sectional study, out of 4617 eyes (2309 subjects) those with refractive errors of <−4 or >+3 dioptres were identified by objective refraction. The iris was examined using the anterior segment mode of a spectral domain 3D OCT‐2000 (Topcon Inc., Japan) in the temporal meridian, and OCT scans were investigated with respect to presence and amount of convex and concave iris configuration. Ninety‐three eyes of 50 subjects served as emmetropic group (−0.5 ≤ x ≤+0.5 dioptres). Previous ocular surgery was exclusion criterion. Results: Six hundred and sixty‐eight eyes of 398 persons [292 male (76%); age range; 18–66 years] were included in the study. In the myopic group, 105 eyes had a concave iris configuration (26%), while in the hyperopic group, no eye had this configuration (0%) and in the emmetropic group five eyes (5%). Convex iris configuration was found in 96% of hyperopic, in 85% of the emmetropic and in 67% of the myopic eyes. There was an association between concave iris configuration and myopia, younger age and male gender, and with anterior chamber angle width. Conclusion: Spectral domain OCT images can be used for analysis of the iris structure and geometry. Our results are limited to the properties of the study population having an age range from 18 to 66 years and consisting mainly of men.